PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MI ATTARAQQIE MALANG - Muhammad Irfan Aziz; Azhar Haq; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractMadrasah leadership is defined as leadership in accordance with the situation to influence subordinates by strengthening confidence, encouragement, cooperation and support to achieve the goals of educational institutions. In this study researchers used the 3 instrument method, namely: interview, observation and documentation. This study aims to describe: the leadership of the madrasah principals in improving the quality of education at MI Attaraqqie Malang, describing the role of the principal in improving the quality of education in Attaraqqie MI Malang and describing the inhibiting factors in improving the quality of education at Attaraqqie MI Malang. While the results of the study show that the role of the headmaster in improving the quality of education as: managers at Malang Attaraqqie MI by empowering education staff through MGWP, workshops, seminars and others, leaders at MI Attaraqqie Malang by establishing good communication with the madrasah community and supervisor at Attaraqqie Malang MI with supervision on the implementation of the learning process. Keywords: The Character Of Headmaster, Quality Of Education.